Effect of silymarin on N-nitrosodiethylamine induced hepatocarcinogenesis in rats - Ramakrishnan, G.; Augustine, T.A.; Jagan, S.; Vinodhkumar, R.; Devaki, T. (Experimental Oncology, 2007)
Aim: To study the effect of silymarin on the levels of tumor markers and MDA (malondialdehyde) – DNA adduct formation during N-nitrosodiethylamine induced hepatocellular carcinoma in male Wistar albino rats. Methods: The levels of AFP, CEA and activities of liver marker enzymes in serum, MDA-DNA immunohistochemistry were done according to standard procedures in the control and experimental groups of rats. Results: Hepatocellular carcinoma was evidenced from significant (p < 0.05) increases of alpha-fetoprotein, carcinoembryonic antigen, aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, acid phosphatase, lactate dehydrogenase, gamma-glutamyltransferase and 5?-nucleotidase in serum and increased MDA-DNA adducts were also observed in the tissue sections of hepatocellular carcinoma. Silymarin treatment significantly attenuated the alteration of these markers and decreased the levels of MDA-DNA adduct formation. Conclusion: Silymarin could be developed as a promising chemotherapeutic adjuvant for the treatment of liver cancer.